Public sector reform in a poor, aid-dependent country, Tanzania - Therkildsen, Ole (2000)
African public sectors went through many changes during the 1960s and 1970s in response to political, economic and social pressures. They expanded in size but remained, at least in design, hierarchical and centralized. Their formal relations to society did not undergo any significant changes either. Generally, the reforms now under way are significantly different from earlier ones. Most are inspired by the new public management (NPM) paradigm. They are also much more radical in their aims, among which are: to reduce the core functions of the state; redraw the boundaries between political and administrative responsibilities; emphasize efficiency; redefine relations between public and private sectors; strengthen accountability; reduce corruption; reorganize organizations and staff; change values and attitudes; and exploit new technologies. This article focuses on a paradox of reform in Tanzania; multiple changes are pursued in the public sector despite fragile domestic political support to the reform package as a whole and despite few service delivery improvements on the ground. It is argued that this is the result of substantial external influences, fragmented domestic policy making, weak links between policy making and implementation, and questionable assumptions about some of the key NPM-inspired reform measures. Moreover, the analyses highlight a number of differences with some of the recent reform literature. - Reproduced
Keywords: Public administration - Tanzania; Administrative reform - Tanzania; Administrative reform